(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Traumatic amputations may be devastating and can result in irreversible functional andpsychological problems in individuals who sustain them. With developmental advances in microvascularsurgery, amputated body parts are now routinely attached in many centres across the world. Successfulreplantation of amputated digits may allow better appearance, better functional outcome and minimal painto the patient.Materials and Methods: This is Prospective observational descriptive study comprising of 20 cases withtraumatic amputation of extremities and its parts treated with replantation and revascularization of part fromOctober 2014 to February 2017. Nature of injury was classified by Yamano classification of amputationbased on mechanism and severity of injury. Patients were evaluated by Chen & Quick DASH score.Results: The viability of replanted part is guranted by a successful vessel anastomosis, while the qualityof bone, tendon, nerve and skin repair will determine the overall functional success of replanted parts.Revascularisation procedures had overall better survival than replantation due to less complexity ofprocedure.